2016
DOI: 10.1111/ddg.12767
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial burden and desire for support in outpatients with skin cancer

Abstract: In addition to their psychosocial burden, patients' desire for support should be assessed. Moreover, apart from screening tools, other ways to provide access to psychosocial care should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
8
0
5
Order By: Relevance
“…found that number to be as high as 71 % . Recently, a similarly high percentage of patients who declined such a program was reported for both outpatients and inpatients at a German SCC .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…found that number to be as high as 71 % . Recently, a similarly high percentage of patients who declined such a program was reported for both outpatients and inpatients at a German SCC .…”
Section: Discussionmentioning
confidence: 89%
“…Ninety‐seven percent of SCCs have already implemented the guideline recommendation to employ standardized screening tools . In this regard, it will be important to have a debate as to how the assessment of the need for psycho‐oncological care may be standardized by using screening tools especially suited for skin cancer patients, and whether it may be necessary to expand the repertoire of recommended screening tools to meet the special requirements of this patient group . This might facilitate future comparison of such surveys among different centers.…”
Section: Discussionmentioning
confidence: 99%
“…wird dieser Patientenanteil mit bis zu 71 % angegeben . Eine ähnliche hohe Ablehnungsquote wurde kürzlich sowohl für ambulante als auch stationäre Patienten eines Hauttumorzentrums in Deutschland berichtet .…”
Section: Diskussionunclassified
“…Die Leitlinienempfehlung zum Einsatz von standardisierten Screeninginstrumenten wird in 97 % der Hautkrebszentren bereits umgesetzt. Im Hinblick darauf wird weiter zu diskutieren sein, wie die Bedarfsermittlung durch den Einsatz besonders für Hautkrebspatienten geeigneter Screeningtools standardisiert werden kann und gegebenenfalls auch das Repertoire der empfohlenen Screeninginstrumente für die speziellen Anforderungen von Hautkrebspatienten erweitert werden muss . Für zukünftige Befragungen dieser Art könnte so die Vergleichbarkeit der Ergebnisse an den Standorten verbessert werden.…”
Section: Diskussionunclassified
“…Buchhold et al. haben vorgeschlagen, dass der Patientenwunsch nach professioneller Unterstützung bei Patienten mit Hautkrebs ebenfalls beurteilt werden sollte, da die psychosoziale Belastung und der Wunsch nach Unterstützung einander oft nicht entsprechen. In jüngster Zeit wurde ein Klassifizierungssystem für den Gesundheitszustand mit mehreren Attributen vorgeschlagen, das den EORTC QLQ‐C30 für Kosten‐Nutzen‐ und gesundheitsökonomische Analysen geeignet macht .…”
Section: Diskussionunclassified